Identification of Colletotrichum acutatum from rubber using random amplified polymorphic DNAs and ribosomal DNA polymorphisms - Saha Thakurdas; Arun Kumar; Bindu Roy; Jacob Kuruvilla; Minimol Ravindran; Nazeer M A (Mycological Research, 2002)
The fungal pathogen responsible for Colletotrichum leaf disease of Hevea, develops three different disease symptoms: raised spots, anthracnose and papery lesions. These diseases have been attributed to Colletotrichum gloeosporioides (teleomorph Glomerella cingulata) and the fungi involved are morphologically indistinguishable. Twenty-five Colletotrichum isolates, which originated from three different disease symptoms, were characterized initially using RAPD markers. Two major RAPD profiles were detected which were related to the type of disease symptom developed. Colletotrichum isolates causing raised spot symptom were easily distinguished from isolates originating from either anthracnose or papery lesions. Restriction analysis of the PCR amplified 5.8S ribosomal DNA (rDNA), including both the flanking internal transcribed spacers (ITS) of representative isolates from the three different disease symptoms, also revealed two distinct RFLP patterns reflecting the same groupings as detected through RAPDs. Both molecular approaches suggested that there were two species of Colletotrichum associated with Hevea inciting the development of three different symptoms: Colletotrichum acutatum causing raised spot symptom, and C. gloeosporioides causing both anthracnose and papery lesions. This is the first record of Colletotrichum acutatum on Hevea in India.
Keywords: Colletotrichum acutatum; DNA polymorphism